INFRASTRUCTURAL RUPTURES: ANXIETIES, BORDERS, AND CLOUDS - Jansen, Fieke; ten Oever, Niels; Baur, Andreas; Cath, Corinne; Jansen, Fieke; Vorndran, Sarah; Maxigas, .; Kalema, Nai (AoIR Selected Papers of Internet Research, 2026)
The rapidly changing geopolitical landscape forces us to rethink the relation between infrastructure, politics, control, and power. This panel contributes to discussions on ruptures by exploring how digital infrastructures reconfigure the state, market, and citizen nexus and presenting research approaches that interrogate transnational networks by centring their materiality. Jointly, the papers showcase how infrastructures are used as a continuation of politics with material means.The authors present five case studies from the global north and south, which foreground the delegation and transfer of power away from states and citizens and the anxiety resulting from this. The papers frame the leveraging of infrastructures in global power relations through the lenses of bordering, infrastructural anxiety, defamiliarization, financialization, and necropolitics. Together, the papers show how the transfer of power to third parties, with their particular agendas and interests, leads to a reconfiguration of control, bringing new challenges to states and citizens.Jointly, the detailed case studies raise questions about initiatives surrounding digital sovereignty, digital public infrastructures, and global internet governance as means of citizen emancipation and their ability to serve the public interest. The panel invites engagement with the development of new infrastructural ideologies to underpin sustainable and equitable futures.The panel is timely because it shows that countries have not (yet) developed an answer to the transition from privatization and globalization to predatory neorealism, which echoes 19th-century conceptions of power that assert that 'might is right'.